Comparison of Ureum and Creatinine Levels Pulmonary Tuberculosis in Phase 0 and 6 Moths Treatment - Aprianto, Aprianto; Sudarsono, Tantri Analisawati; Kusuma Wardani, Dita Pratiwi; Rahaju, Minto (Poltekkes Kemenkes Jakarta III, 2022)
Pulmonary tuberculosis is a disease caused by Mycobacterium tuberculosis. Treatment for tuberculosis patients is given in the intensive and advanced stages. Anti-tuberculosis drugs can be nephrotoxic to cells in the kidneys. This research is an analytic observational study to know the comparison of urea and creatinine levels in pulmonary tuberculosis patients in the 0 and 6-month treatment phases at the Community Lung Health Center Purwokerto. The samples studied were 42 respondents who were taken by accidental sampling. This study was conducted from December 2021 to January 2022. Out of the 42 pulmonary tuberculosis patients who received treatment at 0 and 6 months, the majority of pulmonary tuberculosis patients were 28 patients (66.7%) had normal urea levels, and 38 patients (90.5 %) had normal creatinine levels. Urea levels in pulmonary tuberculosis patients during the 0-month treatment phase were 9 (2-24) mg/dL, while in the 6-month treatment phase, it was 8 (1-37) mg/dL. The creatinine level of pulmonary tuberculosis patients with 0-month treatment phase was 0.98 (0.64-1.62) mg/dL, while in the 6-month treatment phase it was 0.88 (0.62-1.92) mg/dL. There was no significant comparison of urea and creatinine levels in pulmonary tuberculosis patients with treatment phases 0 and 6 months (p>0.05).